Management Measures and Trends of Biological Invasions in Europe: A Survey‐Based Assessment of Local Managers - Carla Garcia‐Lozano; Josep Pueyo‐Ros; Quim Canelles; Guillaume Latombe; Tim Adriaens; Sven Bacher; Ana Cristina Cardoso; Michelle Cleary; Lluís Coromina; Franck Courchamp; Wayne Dawson; Maarten de Groot; et al. (Global Change Biology, 2025)
Biological invasions are a major threat to biodiversity, ecosystem functioning and nature's contributions to people worldwide. However, the effectiveness of invasive alien species (IAS) management measures and the progress toward achieving biodiversity targets remain uncertain due to limited and nonuniform data availability. Management success is usually assessed at a local level and documented in technical reports, often written in languages other than English, which makes such data notoriously difficult to collect at large geographic scales. Here we present the first European assessment of how managers perceive trends in IAS and the effectiveness of management measures to mitigate biological invasions. We developed a structured questionnaire translated into 18 languages and disseminated it to local and regional managers of IAS in Europe. We received responses from 1928 participants from 41 European countries, including 24 European Union (EU) Member States. Our results reveal substantial efforts in IAS monitoring and control, with invasive plants being the primary focus. Yet, there is a general perception of an increase in the numbers, occupied areas, and impacts of IAS across environment and taxonomic groups, particularly plants, over time. This perceived increase is consistent across both EU and non‐EU countries, with respondents from EU countries demonstrating more certainty in their responses. Our results also indicate a lack of data on alien vertebrates and invertebrates, reflecting a need for more targeted monitoring and knowledge sharing between managers and policymakers and between countries. Overall, our study suggests that Europe's current strategies are insufficient to substantially reduce IAS by 2030 and hence to meet the Kunming‐Montreal Global Biodiversity Framework target.

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

Extent and Characteristics of a Newly Discovered Unique Bryozoan Biogenic Reef Complex - Travis Luke Dutka; Alex J. Fejer; Tim Williams; David M. Donnelly; Adrian J. Flynn (Frontiers in Marine Science, 2022)
Using multibeam echosounding (R2Sonic, Austin, Texas) combined with underwater observation and imagery surveys, this study sought to estimate the size and describe the typology of newly discovered biogenic bryozoan reefs in Western Port (VIC, Australia). The bryozoan species forming the biogenic structure are Triphyllozoon moniliferum , T. munitum (both fenestrate forms and dominant on the reef) and Celleporaria (non-fenestrate form and sub-dominant). The bryozoan biogenic reefs occupy a total area of 1.74 km 2 . Their distribution appears to be geomorphically and depth-controlled, which might limit their maximum possible extent. The Western Port bryozoan reefs are unique and globally significant because they: (1) occur in shallow water (typically 5–10 m), (2) are dominated by delicate fenestrate colonies of T. moniliferum and T. munitum , (3) have two distinct morphologies (linear and patch-like), (4) form continuous rows of reef interspersed with fine sediment, and (5) the size and vertical relief (up to approximately 1.5 m) are among the largest recorded in the world. In Western Port, these bryozoan reefs are habitat-forming and may represent sites of enhanced biodiversity, which is currently being investigated in another separate study and are likely important habitat utilised by commercially and recreationally fished species. The bryozoan biogenic reefs are a previously unrecognised feature of conservation significance in this Ramsar site. The reefs are potentially vulnerable to physical damage from recreational fishing practices, sediment smothering and scouring, algal encroachment and hydrological alteration. Recommendations for monitoring and potential management of this unique biotope are made.

Effects of Long‐Term Ungulate Exclusion and Recent Alien Species Control on the Preservation and Restoration of a Hawaiian Tropical Dry Forest - Robert J. Cabin; Stephen G. Weller; David H. Lorence; Tim W. Flynn; Ann K. Sakai; Darren Sandquist; Lisa J. Hadway (Conservation Biology, 2000)
Although the destruction of tropical rain forests receives much attention, tropical dry forests are in general far more threatened and endangered. Eliminating grazing ungulates is often considered a key first step toward protecting these ecosystems, but few studies have investigated the long‐term effects of this technique. We examined the effects of ungulate exclusion from a 2.3‐ha native dry‐forest preserve on the island of Hawaii by comparing its present flora to the flora of an adjacent area subjected to continuous grazing since the preserve was fenced over 40 years ago. Relative to this adjacent area, the fenced preserve contained a more diverse flora with substantially greater coverage of native overstory and understory species. Until recently, however, regeneration of native canopy trees within the preserve appears to have been thwarted by a dominant herbaceous cover of alien fountain grass ( Pennisetum setaceum ) and predation by alien rodent species. Our results indicate that although ungulate exclusion may be a necessary and critical first step, it is not sufficient to adequately preserve and maintain Hawaii's remaining tropical dry forest remnants. Our recent efforts to control the dominant alien species within the fenced preserve suggest that this practice may facilitate both the regeneration of native species and the colonization and potential invasion of new alien plants. Comparisons of seedlings of the dominant native canopy tree Diospyros sandwicensis growing in sites both dominated by and free of fountain grass suggested that fountain grass inhibits Diospyros seedling growth and photosynthesis but may increase survival if seedlings are protected from ungulates.